2023
DOI: 10.1111/1754-9485.13516
|View full text |Cite
|
Sign up to set email alerts
|

Radiology and radiation oncology considerations for transgender and intersex patients: A qualitative study

Abstract: Introduction:In this qualitative study, we explored experiences of radiologists and radiation oncologists in providing clinical care to transgender, gender diverse (TGD), and intersex patients by asking about comfort level, relevant past training and training gaps, and clinical recommendations for TGD and intersex patient care. Methods: A purposive sample of radiology and radiation oncology professionals (n = 16) from diverse practice settings were interviewed on a videoconferencing platform. Transcripts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Meanwhile, a majority of oncologists report that they lack the experience or training to confidently meet the needs of transgender people with cancer ( 11 , 12 ). A qualitative study of radiology and radiation oncology clinicians identified major gaps in training, knowledge, and confidence in caring for transgender people ( 13 ). Prior studies have reported outcomes of cancer treatment in cohorts of transgender patients ( 14 , 15 ), but none have investigated the impact of radiation therapy (RT) on gender-affirming care.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a majority of oncologists report that they lack the experience or training to confidently meet the needs of transgender people with cancer ( 11 , 12 ). A qualitative study of radiology and radiation oncology clinicians identified major gaps in training, knowledge, and confidence in caring for transgender people ( 13 ). Prior studies have reported outcomes of cancer treatment in cohorts of transgender patients ( 14 , 15 ), but none have investigated the impact of radiation therapy (RT) on gender-affirming care.…”
Section: Introductionmentioning
confidence: 99%